Pengaruh Gaya Kepemimpinan,Kerjasama Tim dan Kepuasaan Kerja Terhadap Kinerja Pegawai: Studi Kausal: Di Sekretariat Daerah Kab Nagan Raya - Cut Muzifatul Ummah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze factors that relate to and influence the performance of employees at the regional secretariat of Nagan Raya district. The research was conducted in August and September 2018 with a sample size of 109 participants and 20 respondents to test the research instruments. The sample for this research was taken randomly (simple random sampling). Path analysis (part analysis), using the SPSS version 21 computer, was used to test the empirical hypothesis. The research results show that Leadership Style (X1) has a direct effect on Job Satisfaction (X3) of = 0.382 or 38.2%, Teamwork (X2) has a direct effect on Job Satisfaction (X3) of = 0.380 or 38%, Job Satisfaction (X3 ) has a direct effect on Employee Performance (Y) of = 0.255 or 25.5%, Leadership Style (X1) has a direct effect on Employee Performance (Y) of = 0.238 or 23.8%. Thus, Job Satisfaction is the most dominant variable that can increase the Job Satisfaction of Nagan Raya Regency regional secretariat employees.